Selecting Design Process Modelling Approaches for Building Design: A Review. (May 2022) - Wong, Y. Y. B.; Joyce, S. C.; Blessing, L.
Abstract: Design process modelling is well-founded in fields of mechanical engineering, and product design and development but not in Building Design (BD). This paper looks at the selection process when choosing appropriate models for specific BD processes. The paper adapts process model selection criteria from Trauer's work and combines it with anecdotal evidence from the authors to select these models. The selection criteria were ranked, categorised, and applied to BD processes explained. Process models related to each selection criteria were then selected from backward snowballing of literature.